Biblical leadership : developing church volunteers - Gangel, Kenneth O.; Evangelical Training Association (Wheaton, Ill. : Evangelical Training Association, 2006)
"Empower others to lead biblically. Church leaders today increasingly base their ministries on secular principles rather than the timeless principles of God's Word. This relevant and important book will help you grasp a New Testament picture of leadership that is person-centered and team-centered"--P. [4] of cover.
Accepting and applying biblical leadership -- Paying attention to administration -- Organizing your meaningful ministry -- Setting and achieving goals -- Perceiving and planning ministry -- Creating a climate for developing leadership teams -- Assessing and recruiting leadership teams -- Preparing and placing leadership teams -- Challenging and changing new leaders -- Supervising satisfied teams -- True team decision-making -- Making leaders out of learners.
Includes bibliographical references.
Keywords: Lay ministry; Christian leadership; Church personnel management